Power Management Challenges and Solutions in Advanced Technology Nodes: A Comprehensive Analysis - Desai, NaveenKumar Siddappa (International Journal of Computing and Engineering, 2025)
This article presents a comprehensive analysis of power management challenges and solutions in advanced semiconductor technology nodes, with particular focus on emerging difficulties in sub-nanometer processes. The article examines the intricate relationship between dynamic and static power consumption, interconnect challenges, and thermal management considerations in modern chip design. The article investigates various power reduction techniques, including Multi-Threshold CMOS implementations, advanced transistor architectures, and sophisticated cooling solutions. Through detailed analysis of power delivery networks and thermal constraints, this article demonstrates the effectiveness of various optimization strategies while highlighting the complex trade-offs between performance, power efficiency, and reliability in advanced nodes. The article emphasizes the critical importance of holistic approaches to power management, combining multiple techniques across different design levels to achieve optimal results in contemporary semiconductor devices.